Pengaruh Stres Kerja, Kepuasan Kerja, Dan Komitmen Organsiasi Terhadap Niat Pindah Pekerjaan - Natasha, Gracielle; Ruswanti, Endang (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
Research conducted by Prasetio et al. (2018) found that there was no significant relationship between job stress and job satisfaction. This study aims to examine the relationship between job satisfaction, job stress, organizational commitment and turnover intention. This research was conducted at one of the securities companies in Jakarta named PT. Sucor Sekuritas, which experienced an increase in the number of employees leaving from 2020-2021. The population of this research is the employees of PT. Sucor Sekuritas with a purposive sampling research sample. The source of this research data is secondary data obtained from companies and primary data obtained from a questionnaire survey using google form. The analysis of this research uses Variance based Structural Equation Model using Partial Least Square (Smart-pls) program with an alternative model of covariance based Structural Equation Model with outer model and inner model, as well as descriptive analysis with Three Box Methode. The results obtained in this study are job stress affects the intention to change jobs, job satisfaction and organizational commitment. Then there was no effect of job satisfaction on the intention to change jobs, there was no effect of organizational commitment on the intention to change jobs, and there was no effect of job satisfaction and organizational commitment as intervening variables between job stress and turnover intention.